Pendampingan Pendataan Santri Berbasis Komputerisasi Di Pondok Pesantren Darul Ilmi - Destiartono, Mohamad Egi; Darwanto; Kafabih, An’im; Santosa, Purbayu Budi; Maria, Nugroho Nugroho Sumarjiyanto Benedictus (Yayasan Sagita Akademia Maju, 2024)
Data play an important role in mapping problems, potentials, and long-term plans of an institution, including Islamic boarding schools. This Community Service (PKM) activity aims to socialize the importance of computer-based data management through the use of Microsoft Excel, Google Forms, and Bitly. This community service activity was carried out at the Darul Ilmi Islamic boarding school, Meteseh Village, Semarang. Community service was conducted through three approaches: (i) field observation, (ii) interactive socialization, and (iii) mentoring/training. Field observations were applied to collect problems that existed at the location and potential that could be developed. Socialization was carried out by providing material on